A two-stage decoder for pragmatic trellis-coded M-PSK modulation using a symbol transformation. - Morelos-Zaragoza, R.H.
A two-stage decoding procedure for pragmatic trellis-coded modulation (TCM) is introduced. It applies a transformation from the received I-channel and Q-channel samples onto points in a two-dimensional (2-D) signal space that contains a coset constellation. For pragmatic TCM over M-PSK signal sets with ν coded bits per symbol, ν=1, 2, the signal points in the coset constellations represent cosets of a B/QPSK signal subset-associated with the coded bits-in the original M-PSK signal constellation. A conventional Viterbi decoder operates on the transformed symbols to estimate the coded bits. After reencoding these bits, the uncoded bits are estimated in a second stage, on a symbol-by-symbol basis, with decisions based on the location of the received symbols. In addition to requiring no changes in the Viterbi decoder core, it is shown that the proposed method results in savings of up to 40% in the memory required to store (or in the size of the logic required to compute) metrics and transformed symbols
Keywords: 2D signal space; BPSK signal subset; Q-channel sample; QPSK signal subset; TCM; Coded bits; Coset constellation; Coset constellations; Pragmatic trellis-coded M-PSK modulation; Received I-channel.; Received symbols; Reencoding; Signal points; Symbol transformation; Transformation; Transformed symbols; Two-stage decoder; Uncoded bits